Atomic charges of sulfur in ionic liquids: experiments and calculations. (25th October 2017) - Fogarty, Richard M.; Rowe, Rebecca; Matthews, Richard P.; Clough, Matthew T.; Ashworth, Claire R.; Brandt, Agnieszka; Corbett, Paul J.; Palgrave, Robert G.; Smith, Emily F.; Bourne, Richard A.; Chamberlain, Thomas W.; Thompson, Paul B. J.; et al.
Abstract : A wide variety of experimental and computational methods are used to probe sulfur atomic charges in ionic liquids. Abstract : Experimental near edge X-ray absorption fine structure (NEXAFS) spectra, X-ray photoelectron (XP) spectra and Auger electron spectra are reported for sulfur in ionic liquids (ILs) with a range of chemical structures. These values provide experimental measures of the atomic charge in each IL and enable the evaluation of the suitability of NEXAFS spectroscopy and XPS for probing the relative atomic charge of sulfur. In addition, we use Auger electron spectroscopy to show that when XPS binding energies differ by less than 0.5 eV, conclusions on atomic charge should be treated with caution. Our experimental data provides a benchmark for calculations of the atomic charge of sulfur obtained using different methods. Atomic charges were computed for lone ions and ion pairs, both in the gas phase (GP) and in a solvation model (SMD), with a wide range of ion pair conformers considered. Three methods were used to compute the atomic charges: charges from the electrostatic potential using a grid based method (ChelpG), natural bond orbital (NBO) population analysis and Bader's atoms in molecules (AIM) approach. By comparing the experimental and calculated measures of the atomic charge of sulfur, we provide an order for the sulfur atoms, ranging from the most negative to the most positive atomic charge. Furthermore, we show that both ChelpG and NBO are reasonable methods for calculating the atomic charge of sulfur in ILs, based on the agreement with both the XPS and NEXAFS spectroscopy results. However, the atomic charges of sulfur derived from ChelpG are found to display significant, non-physical conformational dependence. Only small differences in individual atomic charge of sulfur were observed between lone ion (GP) and ion pair IL(SMD) model systems, indicating that ion–ion interactions do not strongly influence individual atomic charges.